(untitled) (Journal of Educational Sciences, 2022)
Today, preparing future teachers for the use of digital educational resources is the most pressing issue of Higher Education. They contribute to the effective organization of the educational process in accordance with the requirements of the modern information society, but also become a universal tool for the harmonious adaptation of students to a rapidly changing information society, training the personality of a competent specialist capable of professional self-realization. First of all, digital educational resources are ready-made interactive multimedia products aimed at achieving a didactic goal or solving certain educational tasks. Currently, the effectiveness of their use is not only to generate interest in the information educational environment, but also to ensure the degree of access to information and improve the quality of Education. Using digital educational resources, the authors independently develop the intellectual potential of students and increase the knowledge base.Using them creatively, we tried to find out whether it is possible to present the educational process in an interesting and informative way. The article provides a comprehensive analysis of the theoretical and methodological literature, clarifies the following concepts and offers a definition: "digital educational resources ", " readiness of a future teacher to use digital educational resources". In addition, during the practical experiment, a course program "digital educational resources-a tool for professional self - development" was developed, aimed at forming the assimilation of digital educational resources by future specialists as a tool for professional self-development. The research uses theoretical, Emeric methods, the questionnaire "knowledge of digital educational resources" (in author’s processing), N. P. Fetiskin "diagnostics of the implementation of needs for professional self-development", N. R. Molochnikov "assessment of opportunities for self-development". 82 students of Atyrau University took part in the experimental work Keywords: digitalization of education, digital educational resources, computer, multimedia, interactivity, accessibility.